An energy efficiency solution for WBAN in healthcare monitoring system - De-Thu Huynh; Min Chen (2016 3rd International Conference on Systems and Informatics (ICSAI), 2016)
The Wireless Body Area Network (WBAN) allows Healthcare Monitoring Systems to get the flexibility and mobility characteristics. However, almost WBAN is made up of several tiny, light-weighted and battery-operated sensors with the limit of energy. Therefore, an energy-effective WBAN system is vitally important to make the long-term Healthcare Monitoring System. In this paper, we have proposed an energy efficiency solution for WBAN based on ZigBee applying Healthcare Monitoring System. Particularly, we utilized the ZigBee standard working in beacon-enable mode to obtain the adaptive duty cycle. Consequently, the energy consumption in idle-mode is avoided, as well as the total energy consumption of sensors is also decreased and extended network lifetime. The simulation results conducted by OPNET Modeler show that our proposed method can save efficient energy consumption of WBAN while the QoS is ensured in terms of network performances (e.g., average end to end delay, network throughput) in long-term Healthcare Monitoring System.